2012
DOI: 10.1039/c1ob06535a
|View full text |Cite
|
Sign up to set email alerts
|

A novel D-ring modified taxoid: synthesis and biological evaluation of a γ-lactone analogue of docetaxel

Abstract: The synthesis of a novel D-ring modified docetaxel analogue, in which the oxetane ring is replaced with a γ-lactone, was achieved from 10-deacetylbaccatin III. The key steps of the synthesis include the direct acetylation of the secondary hydroxyl group at C-5 and D-ring opening and intramolecular aldol reaction to form the γ-lactone. In MTT assays, this analogue proved to have equipotent cytotoxicity relative to paclitaxel towards HCT8, HePG2 and BGC23 cancer cell lines, and be more potent than paclitaxel aga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 16 publications
0
5
0
Order By: Relevance
“…Acetylation at OH-3 would lead to an acetylated product at this position that could undergo a cyclization into a γ -lactone on a ketone at C-2 ( Scheme 1 ). Oxidation at positions C-2 or C-3 have already been observed [ 40 ], and such a nucleophilic addition of a methyl ester on an adjacent ketone was demonstrated synthetically in strongly basic conditions with a derivative of taxol [ 41 ]. An enzyme could catalyze the addition reaction in the case of this natural product and impose the observed stereochemistry.…”
Section: Resultsmentioning
confidence: 99%
“…Acetylation at OH-3 would lead to an acetylated product at this position that could undergo a cyclization into a γ -lactone on a ketone at C-2 ( Scheme 1 ). Oxidation at positions C-2 or C-3 have already been observed [ 40 ], and such a nucleophilic addition of a methyl ester on an adjacent ketone was demonstrated synthetically in strongly basic conditions with a derivative of taxol [ 41 ]. An enzyme could catalyze the addition reaction in the case of this natural product and impose the observed stereochemistry.…”
Section: Resultsmentioning
confidence: 99%
“…The assembly and disassembly of aand b-tubulins lead to polymerization of microtubules, and it is very important for chromosomal segregation during mitosis. Since anticancer activity of vinca alkaloids (e.g., 1 and 2), colchicine (3), and paclitaxel (4) are attractive to chemists and biologists, several derivatives of these drugs have been prepared and investigated for anticancer activity [19][20][21][22][23][24][25][26][27]. Cancer cell growth can be inhibited either by the inhibition of tubulin polymerization or the promotion of tubulin polymerization.…”
Section: Tubulin/microtubule-targeted Anticancer Agentsmentioning
confidence: 99%
“…A phase II clinical trial of 17-AAG (22) showed a significant anticancer activity in patients with HER2-positive metastatic breast cancer [65]. Recently, 19-substituted geldanamycin derivatives (24)(25)(26)(27)(28)(29) were synthesized ( Fig. Although several semisynthetic geldanamycin derivatives were prepared and evaluated for Hsp90 inhibitory activity, the structure modifications were mostly performed at the C-17 position of 21.…”
Section: Heat Shock Protein 90 Inhibitors As Anticancer Agentsmentioning
confidence: 99%
“…With our continuous interest in ynone transformations, we envisioned that through catalytic σ-activation, the formal [4 + 2] cyclization between 2-aminobenzaldehydes and CF 3 -ynones [8] could generate a range of 2-arylquinoline derivatives (Scheme 2, top). Based on this, a series of important 2arylquinoline scaffolds were assembled through a Mgcatalyzed [9] [4 + 2] annulation reaction between 2aminobenzaldehydes and ynones (Scheme 2, bottom).…”
Section: Introductionmentioning
confidence: 99%